Innovation at the end of the life cycle: discontinuous innovation strategies by incumbents. Issue 3 (3rd April 2017) - Kishna, Maikel; Negro, Simona; Alkemade, Floortje; Hekkert, Marko
Abstract: This paper focuses on the strategies of incumbents that seek to develop discontinuous innovations within the boundaries of a mature innovation system. Mature innovation systems do not provide support for these discontinuous innovations. This article focuses on exploring why incumbents in these setting engage in discontinuous innovation and what strategies they deploy to become successful. We analyse 10 cases of incumbents developing discontinuous innovations in the mature Dutch greenhouse horticulture sector. The results of our analysis show that the incumbents are primarily triggered by dissatisfaction with the current way of doing business and that the existing institutions are the main barrier to discontinuous innovation. In response, the incumbents try to circumvent the existing innovation system in their innovation process, but when successful also engage in changing the existing innovation system. This paper contributes to the understanding of the role of incumbents as source of discontinuous innovation in mature innovation systems.